G. Stanley Hall correspondence - Hall, G. Stanley (Granville Stanley), 1844-1924.
ALS (1896 January 2) written by Hall to George Willis Cooke recommending several works on psychology.
Psychologist and educator.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Cooke, George Willis, -- 1848-1923 -- Correspondence; Psychology; Educators; Psychologists